Analysis on aerodynamic performance based on optimization of automobile head shape. Issue 3 (March 2019) - Wang, Xuechao; Lu, Qiang; Li, Renzheng; Xu, Xiaoming
Abstract: Aerodynamics characteristic parameters are the important parameters that affect the performance of automobile, such as dynamic performance, economic performance and control stability, which play an important role in automobile appearance design. In this paper, FLUENT software was used to simulate the simple models with different head shapes and study the aerodynamic characteristics, so as to optimize the automobile modeling and improve the aerodynamic performance.